Native Providence : memory, community, and survivance in the Northeast - Rubertone, Patricia E. (University of Nebraska Press, 2020)
"Native Providence reveals stories of Native urban life in the Northeast United States shaped by the dynamics of colonialism, race, and class, and not in the least by the survivance of people who today still live among the ruins of modernity"--